FUNctional Ceramics - Fineman, Jeremy A. (East Carolina University, 2011)
As a potter who deals with consumer products, I use different approaches in my making process to practice methods that have less of an impact on the Earth's resources. In this thesis, I will be investigating two different perspectives to achieve this.   Repurposing once used vegetable oil as a fuel for firing the kiln and designing a burner that is efficient and reliable, I have attempted to lessen the impact that manufacturing ceramic pots has on the ecosystem. The values that I hold about the environment are reflected in the practice of making pots with an ethically sound approach.  Creating ceramic products that incorporate elements of play into the ergonomics of the pieces, I am investigating the concept of humor as a tool to establish better practices within my community. Using adapted methodologies, the ceramics vessels that I produce invite a communication to take place between the user and myself.
Keywords: Fine arts; Biogeochemistry; Environmental studies; Bullfrogtoes; Burners; Ceremonies; Kiln building; Repurposed vegetable oil; Kilns; Ceramics; Firing (Ceramics); Pottery--Environmental aspects